Influences on food choices of urban Chinese teenagers. Issue 4 (11th November 2014) - Veeck, Ann; Grace Yu, Fang; Yu, Hongyan; Veeck, Gregory; W. Gentry, James
Abstract : Purpose: – This study aims to examine the major influences of food choices of Chinese teenagers within a dynamic food marketing environment. Design/methodology/approach: – The paper reports findings from semi-structured interviews with high school students which examine teenagers' guidelines for selecting food, along with their actual eating behavior. Findings: – The results reflect on how four major influences – personal, family, peer and retailer – may intersect to affect the eating behaviors of Chinese adolescents, as they navigate an intense education schedule during a time of rapidly changing cultural values. Different norms of food choice – nutrition, food safety, taste, body image, price, convenience, sharing, friendship and fun – are evoked according to the social context and concurrent activities of the teenagers. Social implications: – The findings offer tentative insights related to the potential for promoting healthier eating habits for adolescents in urban areas of China. Originality/value: – The study demonstrates how, within this rapidly changing food environment, food retailers are creating alliances with teenagers to meet needs of convenience, speed, taste and social interaction.